(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
In this thesis, the emergence of the field of machine translation as a result of the integration of the fields of computer technology and translation studies, the directions of this field and the problems of corpus-based machine translation, that is, inconsistencies in the translation of phraseological units in works of art into another language, and the use of works of art in solving these problems the linguistic importance of creating bilingual or multilingual parallel corpora and creating a dictionary of phraseological units based on them is highlighted.